SOSIALISASI PENCEGAHAN BULLYING MELALUI PENDEKATAN GAMES INTERAKTIF DI SDN 3 SELAAWI - Fikriaini, Amalia; Kurniasih, Nunung; Supendi, Dede (Jurnal Pemberdayaan Masyarakat dan Inovasi, 2025)
Bullying is an act of harm directed at a person or group in psychological, physical, or verbal form. Efforts to overcome bullying behavior can be done in various ways, one of which is by socialization. The challenge that occurs in the field during socialization is the way of delivering material that is less interesting, therefore an approach with interactive games is needed so that activities do not make students bored. This community service activity is carried out using the Participatory Action Research (PAR) method which aims to prevent bullying in the school environment in an interesting way for students in elementary schools. The results of socialization activities with this approach went smoothly, this can be seen from the faces and active participation of students during the socialization. Through this socialization, students can understand the concept of bullying and how to prevent it. And it is hoped that schools can carry out regular prevention through an interactive game approach as a prevention effort and teach in an interesting way for students so that they can protect themselves from potential bullying that exists outside of school.